Prints + Multiples : 79th Exhibition by Artists of Chicago and Vicinity. - The Art Institute of Chicago; Lakeview Museum of the Arts and Sciences, Peoria; National Academy of Design, New York; National Museum of American Art, Smithsonian Institution, Washington; Illinois State Museum, Springfield; Quincy Society of Fine Arts, Quincy (Chicago : The Art Institute of Chicago, 1981)
Brown, Greg ; Almeida, Peter ; Altman, Edith ; Berdich, Vera ; Bernstein, Gerda Meyer ; Brakke, Michael ; Brams, Krimmer ; Bramson, Phyllis ; Brown, Nadya ; Brown, Roger ; Bujnowski, Joel ; Bushman, David F. ; Calvin, Jane L. ; Carroll, William ; etc.
Prints + Multiples : 79th Exhibition by Artists of Chicago and Vicinity, The Art Institute of Chicago, July 4 - August 16, 1981 / Lakeview Museum, Peoria, October 4 - November 15, 1981 / National Academy of Design, New York, January 19 - February 21, 1982 / National Museum of American Art, Smithsonian Institution, Washington, May 19 - August 21, 1982 / Illinois State Museum, Springfield, September 12-23, 1982 / Quincy Society of Fine Arts and Quincy Art Club, Quincy, December 13, 1982 - January 23, 1983 / etc.
boek